Α‐Adrenergic receptor blockade attenuates pressor response during mental stress in young black adults. Issue 24 (23rd December 2020) - Jeong, Jin Hee; Brown, Michelle L.; Kapuku, Gaston; Harshfield, Gregory A.; Park, Jeanie
Abstract: Black individuals exhibit increased blood pressure (BP) responses to sympathetic stimulation that are associated with an increased risk of hypertension (HTN). We tested the hypothesis that α1 ‐adrenergic blockade inhibits the increased BP response during and after 45‐min stress in young normotensive Black adults, which may be mediated, in part, by dampened vasoconstriction and decreased renal sodium retention. Utilizing a double‐masked randomized, crossover study design, 51 normotensive Black adults (31 ± 8 yr) were treated with either a placebo or 1 mg/day of prazosin for 1 week. On the final day of each treatment, hemodynamic measures and urinary sodium excretion (UNaV) were collected before (Rest), during (Stress) and after (Recovery) 45 min of mental stress induced via a competitive video game task. During the Stress period, diastolic BP and total peripheral resistance (TPR) were significantly lower with prazosin compared to placebo ( p  < .05 for both). Similarly, we observed lower systolic BP, diastolic BP, and TPR during the Recovery period with prazosin versus placebo ( p  < .05 for both). There was no effect of prazosin on stress‐associated UNaV. The change in systolic BP from Rest to Recovery was positively associated with the change in TPR with both treatments ( p  < .05 for both). In summary, prazosin treatment dampened BP reactivity to 45‐min mental stress and lowered post‐stress BP over the recovery period, which was linked to reduce TPR in young normotensive Black adults. These results suggest that α1 ‐adrenergic receptor activity may contribute to BP responses and delayed BP recovery to prolonged mental stress through increased vasoconstriction in Black adults. Abstract : Psychological stress contributes to the susceptibility and severity of hypertension. Black individuals are known to elicit hyper‐hemodynamic responsiveness to various stressors. The present study demonstrated that the blockage of alpha‐adrenergic receptor activity improved the blood pressure responses to mental stress in young normotensive Black adults.